Method for regulating and controlling crystal form of medicine through oxidized nanocellulose and application

By mixing oxidized nanocellulose with the drug in solution, nucleation and growth of the drug crystal form is regulated, and the problem of lack of accuracy and controllability of drug crystal form control in the prior art is solved, efficient, repeatable and predictable control of drug crystal form is achieved, and the solubility, stability and bioavailability of the drug are improved.

CN119528842AActive Publication Date: 2025-02-28SHANGHAI UNIV OF ENG SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411502135.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The prior art lacks accuracy and controllability in drug crystal form control, making it difficult to ensure the stability and repeatability of specific crystal forms, and cannot meet the needs of drug research and development for efficient, repeatable and predictable crystal form control.

Method used

By using oxidized nanocellulose (TCNF) as polymer material, mixed with the drug in solution, nucleation and growth of the drug crystal form is regulated, and precise control of the drug crystal form is achieved by adjusting the concentration of TCNF and the supersaturation of the drug.

Benefits of technology

It achieves efficient, repeatable and predictable control of drug crystal forms, improves drug solubility, stability and bioavailability, and is suitable for the development of polycrystalline drugs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528842A_ABST
    Figure CN119528842A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of chemical engineering and medicine manufacturing, and particularly relates to a method for regulating and controlling a medicine crystal form through oxidized nanocellulose and application. The generation of the sulfathiazole crystal is induced in TCNF solutions with different concentrations, and the nucleation and growth process of the sulfathiazole crystal is controlled, so that the sulfathiazole crystal forms with different forms and structures are obtained, and the conversion of the sulfathiazole crystal from a sheet shape and a prism shape to a regular hexahedron crystal form is realized. The sulfathiazole crystal form prepared by the method disclosed by the invention has better crystal form and consistency, and the method disclosed by the invention is simple, effective and suitable for crystal form optimization and large-scale production of polymorphic drugs, and has important industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical engineering and drug manufacturing, and specifically relates to a method for regulating drug crystal form by oxidizing nanocellulose and its application. Background Art

[0002] The crystal form of a drug is one of the important characteristics of the solid form of the drug. It not only determines the physical and chemical properties of the drug, but also has a significant impact on the preparation process, stability, solubility and bioavailability of the drug. In the process of drug development, crystal form control has always been a research field that has received much attention. By controlling the crystal form of the drug, the stability and solubility of the drug can be optimized, thereby improving the efficacy of the drug. However, crystal form control faces many challenges in actual operation, especially when obtaining polymorphs with stable structures and superior performance, which often requires complex processes and conditions.

[0003] Traditionally, the crystal form of a drug is mainly obtained by crystallizing under different conditions, such as changing the type, concentration, temperature and crystallization rate of the solvent. The basis of these methods is to induce the formation of different crystal structures by rearranging the solute molecules. However, this method often relies on changes in the external environment, lacks precise control, and the generation of crystal forms is random. In addition, the generation of different crystal forms often depends on the experience of the experimenter, and because different crystal forms compete with each other in the solution, it is difficult to ensure the stability and repeatability of a specific crystal form. Therefore, in the field of crystal form control, relying on simple changes in physical conditions can no longer meet the current drug development needs for efficient, repeatable and predictable crystal form control.

[0004] In recent years, with the rapid development of nanotechnology and molecular materials science, polymer-induced drug crystal form control has gradually become an emerging research direction. Polymers can selectively bind to drug molecules through intermolecular interactions to regulate the nucleation and growth of drug crystals. This molecular-level crystal form control method has higher accuracy and controllability than the traditional physical condition change method. For example, common polymers such as polyvinyl pyrrolidone (PVP) and polyethylene glycol (PEG) are widely used in drug crystal form control. Through hydrogen bonds and van der Waals forces between drug molecules, they can effectively affect the formation of crystal forms. Especially in the development of polymorphic drugs, polymer-induced methods provide a new way to discover new crystal forms and improve drug performance.

[0005] An important background of the present invention is the recent research on the crystal form of drugs such as sulfathiazole. Sulfathiazole is a drug commonly used in antibacterial treatment, and its polymorphic properties have also attracted much attention. This study found that the crystal form of these drugs can be effectively controlled through the polymer induction method. Summary of the invention

[0006] The present invention provides a method for regulating drug crystal form by polymer, through which the drug crystal form is induced and controlled, and the physical and chemical properties of the drug, such as solubility, stability and bioavailability, are improved. The core of the present invention is to control the generation and stability of drug crystal form by selecting suitable polymer materials (such as oxidized nanocellulose) and combining crystallization process. The method of the present invention is suitable for the development of polymorphic drugs, and can effectively induce the generation of polymorphs with excellent properties by regulating the concentration of polymer materials.

[0007] The technical solution of the present invention is that the present invention provides an application of oxidized nanocellulose TCNF to regulate the crystal form of drugs.

[0008] The present invention provides a method for regulating drug crystal form by oxidizing nanocellulose TCNF, the steps comprising: mixing a drug and an oxidized nanocellulose material in a solution to crystallize; the drug is in a supersaturated state in the solution, and the nucleation and growth of the drug crystal form are controlled by regulating the concentration of the oxidized nanocellulose material.

[0009] Further, the oxidized nanocellulose material solution is mixed with the drug and crystallized.

[0010] The concentration of the oxidized nanocellulose material is 0.1wt%-1wt%, preferably 0.5wt%-1wt%, more preferably 0.8wt%-1wt%; the supersaturation S of the drug is 1-8, preferably 3-5. The mass ratio of the drug to the oxidized nanocellulose is 1:0.5-10, preferably 1:4-8, more preferably 1:7-8.

[0011] The drug includes sulfathiazole, a drug having a sulfathiazole mother core or a sulfathiazole-like mother core, and a drug having a p-aminobenzenesulfonamide mother core or a p-aminobenzenesulfonamide-like mother core. The drug having a sulfathiazole mother core or a sulfathiazole-like mother core may be a drug that introduces other functional groups on sulfathiazole, or a relative position of an amino group and a sulfonamide group may be changed, or other functional groups may be introduced on a benzene ring or a thiazole ring, or one or several elements on sulfathiazole may be replaced, and the like, and the crystal form regulation effect similar to sulfathiazole is produced when it is combined with a polymer material. The drug having a p-aminobenzenesulfonamide mother core or a p-aminobenzenesulfonamide-like mother core may be a drug that introduces other functional groups on a p-aminobenzenesulfonamide mother core, or a relative position of an amino group and a sulfonamide group may be changed, or other functional groups may be introduced on a benzene ring or an amino group or a sulfonamide group, or one or several elements on p-aminobenzenesulfonamide may be replaced, and the crystal form regulation effect similar to sulfathiazole is produced when it is combined with a polymer material. Specific examples include sulfamethoxazole, sulfadiazine, sulfamethoxazole, and the like.

[0012] The concentration of the oxidized nanocellulose TCNF solution is 0.1wt%-1wt%, preferably 0.5wt%-1wt%, and more preferably 0.8wt%-1wt%. By adjusting the concentration of the oxidized nanocellulose TCNF, the sulfathiazole crystals gradually change from flake and prism to regular hexagonal morphology, and the morphology of the crystals is closely related to the concentration of the oxidized nanocellulose.

[0013] In the process of regulating the crystal form of the drug by oxidizing nanocellulose, the drug and the oxidized nanocellulose material are mixed in a solution, stirred, and evenly mixed.

[0014] In the process of regulating the crystal form of the drug by oxidizing nanocellulose, the crystallization method is ice bath cooling crystallization, specifically, crystallization is performed by cooling the ice bath to room temperature.

[0015] The preparation method of oxidized nanocellulose TCNF solution includes: dispersing the raw material of oxidized nanocellulose in water, adding 2,2,6,6-tetramethylpiperidine-1-oxyl, sodium bromide and sodium hypochlorite to react, then adding ethanol to terminate the reaction, washing with water to neutrality, and obtaining oxidized nanocellulose TCNF solution.

[0016] The raw material of the oxidized nanocellulose includes any one or any combination of pulp, cotton, wood, straw, etc., and the cotton, wood, straw, etc. are pretreated first. The mass ratio of the raw material of the oxidized nanocellulose to water is 1:100-300, preferably 1:150.

[0017] The mass ratio of 2,2,6,6-tetramethylpiperidin-1-oxyl, sodium bromide and pulp is 0.01-0.02:0.05-0.3:1, preferably 0.016:0.1:1.

[0018] The volume mass ratio of sodium hypochlorite to pulp is 6-7 mL: 1 g, preferably 6.7 mL: 1 g, and the sodium hypochlorite is 13% sodium hypochlorite.

[0019] During the preparation of the oxidized nanocellulose TCNF solution, 2,2,6,6-tetramethylpiperidin-1-oxyl and sodium bromide were first added, and then sodium hypochlorite was slowly added.

[0020] During the preparation of the oxidized nanocellulose TCNF solution, the reaction temperature is room temperature, preferably 25° C., and the reaction time is 4 hours.

[0021] During the preparation of the oxidized nanocellulose TCNF solution, the solution was washed with water until neutral, then ultrasonically suspended and concentrated.

[0022] The present invention finds that when preparing oxidized nanocellulose (TCNF) suspension, carboxyl groups are introduced by TEMPO oxidation. This oxidation process enables the cellulose material to obtain good water solubility and a stable three-dimensional network structure, thereby providing an effective steric hindrance effect in the drug crystallization process.

[0023] There are significant differences in the morphology and crystal form of sulfathiazole crystals under different TCNF concentrations. Under low TCNF concentration conditions (such as 0.1wt%), the sulfathiazole crystal form is mainly hexagonal flakes and prismatic crystals. With the increase of TCNF concentration, the crystals gradually transform into hexagonal crystals, and at a TCNF concentration of 1.0wt%, sulfathiazole mainly forms uniform, regular hexagonal crystals, indicating that the steric hindrance effect of TCNF has a significant regulatory effect on the crystal morphology.

[0024] The results of X-ray powder diffraction (PXRD) showed that the crystal forms induced by different concentrations of TCNF had different diffraction peaks. Especially when the concentration of TCNF was high, the crystal form of sulfathiazole mainly showed the characteristic peaks of crystal form III. In addition, the results of Fourier transform infrared spectroscopy (FTIR) spectral analysis showed that in high-concentration TCNF solution, the carboxyl and hydroxyl groups in the sulfathiazole crystals formed a strong interaction with the cellulose material, and this interaction further stabilized the crystal structure of sulfathiazole.

[0025] The main advantages of the present invention include:

[0026] 1. Wide range of applications

[0027] The method of the present invention is applicable to the crystal form control of various drugs, especially for drugs with polymorphic forms, and has a significant effect. In addition to sulfathiazole, the present invention can also be applied to other sulfonamide drugs with similar parent core structures or functional groups, and the effective regulation of the crystal forms of these drugs can be achieved by similar methods. At the same time, the method of the present invention can also be extended to other drugs, especially those with similar chemical behaviors in crystal form control, providing a highly versatile technical solution for the field of drug crystal form regulation.

[0028] 2. Simple process, easy to implement

[0029] The method of the present invention is based on conventional drug preparation technology and is easy to implement in existing production lines. The polymer material is low in cost, the experimental operation is simple, and it has a high industrial application prospect.

[0030] 3. Environmentally friendly and biocompatible

[0031] TEMPO oxidized cellulose is an environmentally friendly material derived from natural cellulose, and has good biocompatibility and degradability. This makes the material used in the present invention not only environmentally friendly, but also suitable for the pharmaceutical industry, and meets the requirements of green chemistry and biocompatible drug production.

[0032] 4. Reduce the uncertainty of crystal formation

[0033] The present invention can reduce the uncertainty in the crystal formation process by using oxidized nanocellulose, and enhance the repeatability and consistency of the crystal form. By controlling the added concentration of the polymer and the supersaturation of the drug solution, it can ensure that the same crystal form results can be obtained in each experiment or production, thereby improving the consistency of drug production and the quality control level.

[0034] In summary, the present invention provides a method for controlling the crystal form of a drug by polymer induction, which can effectively improve the solubility, stability and bioavailability of the drug, and is particularly suitable for the crystal form optimization and regulation of polymorphic drugs. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of the structure of sulfathiazole molecule and oxidized nanocellulose.

[0036] Figure 2 The FTIR spectra of pulp and oxidized nanocellulose are shown in Figure 2. The characteristic absorption peaks of pulp and oxidized cellulose appear at 1050 cm-1, 1630 cm-1, 2920 cm-1 and 3442 cm-1, which are related to OH stretching vibration and asymmetric CH stretching vibration, respectively. The absorption peak at 1728 cm-1 was observed in the spectrum of oxidized cellulose, representing the stretching vibration of the carboxyl group, indicating that the carboxyl group was successfully introduced into the oxidized nanocellulose, and the carboxyl functional group affected the crystal nucleation and growth of sulfathiazole.

[0037] Figure 3 These are three crystal forms of sulfathiazole crystallized under cooling conditions in water.

[0038] Figure 4 This is the XRD pattern of sulfathiazole in water, which is a mixture of three crystal forms: II, III and IV. II is square, III is prismatic, and IV is flat hexagonal.

[0039] Figure 5The experimental results of oxidized nanocellulose at different concentrations on the crystal form of sulfathiazole. a is the XRD pattern of sulfathiazole crystals generated in water, 0.1wt% TCNF solution, 0.3wt% TCNF solution, 0.5wt% TCNF solution, and 1.0wt% TCNF solution, b is the XRD pattern of sulfathiazole crystals generated in 0.1wt% TCNF solution, c is the XRD pattern of sulfathiazole crystals generated in 0.3wt% TCNF solution, d is the XRD pattern of sulfathiazole crystals generated in 0.5wt% TCNF solution, and e is the XRD pattern of sulfathiazole crystals generated in 1.0wt% TCNF solution. DETAILED DESCRIPTION

[0040] Example 1 Preparation of TEMPO-oxidized nanocellulose

[0041] 6 g of pulp was dispersed in 900 mL of water to form a suspension. 0.096 g of 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) and 0.6 g of sodium bromide (NaBr) were added to the suspension, and 40 mL of sodium hypochlorite solution (NaClO, 13%) was slowly added to the suspension, the reaction temperature was controlled at 25 ° C, and stirred for 4 hours. After the reaction, ethanol was used to terminate the reaction, and the precipitate was washed with water until neutral to obtain a TEMPO oxidized nanocellulose (TCNF) suspension. The TCNF suspension was treated with ultrasound and concentrated to obtain a uniform 1 wt% TCNF solution.

[0042] The 1 wt% TCNF solution was diluted with water to obtain 0.1 wt%, 0.3 wt% and 0.5 wt% TCNF solutions respectively.

[0043] Example 2 Preparation and Control of Sulfathiazole Crystalline Form (0.1wt%, Low Concentration TCNF Solution)

[0044] (1) TCNF-induced crystal formation

[0045] 20 mg of sulfathiazole (S=4.85) was added to 16 mL of 0.1 wt% TCNF solution, and after uniform stirring, the mixture was placed in an ice bath and cooled to room temperature to allow natural crystallization.

[0046] (2) Crystal separation and drying

[0047] After 12 hours of crystallization, the crystals were separated with filter paper and washed with distilled water. The crystals were vacuum dried at 40°C for 24 hours to obtain sulfathiazole crystal samples. The results showed that under 0.1wt% TCNF conditions, sulfathiazole crystals were in the form of flakes or prisms. Figure 5 As shown, its composition includes II crystal form, III crystal form and IV crystal form.

[0048] Example 3 Preparation and Control of Sulfathiazole Crystalline Form (0.3wt%, Low Concentration TCNF Solution)

[0049] (1) TCNF-induced crystal formation

[0050] 20 mg of sulfathiazole (S=4.85) was added to 16 mL of 0.3 wt% TCNF solution, and after uniform stirring, the solution was placed in an ice bath and cooled to room temperature to allow natural crystallization.

[0051] (2) Crystal separation and drying

[0052] After 12 hours of crystallization, the crystals were separated with filter paper and washed with distilled water. The crystals were vacuum dried at 40°C for 24 hours to obtain sulfathiazole crystal samples. The results showed that under 0.3wt% TCNF conditions, sulfathiazole crystals were in the form of flakes or prisms. Figure 5 As shown, its composition is III crystal form.

[0053] Example 4 Preparation and Control of Sulfathiazole Crystalline Form (0.5wt%, Medium Concentration TCNF Solution)

[0054] (1) TCNF-induced crystal formation

[0055] 20 mg of sulfathiazole (S=4.85) was added to 16 mL of 0.5 wt% TCNF solution, and after uniform stirring, the solution was placed in an ice bath and cooled to room temperature to allow natural crystallization.

[0056] (2) Crystal separation and drying

[0057] After the crystals were crystallized, they were separated with filter paper and washed with distilled water for several times. The crystals were vacuum dried at 40°C for 24 hours to obtain sulfathiazole crystal samples. The results showed that under the condition of 0.5wt% TCNF, the sulfathiazole crystal morphology began to change to hexagonal shape. Figure 5 As shown, its composition is III crystal form.

[0058] Example 5 Preparation and Control of Sulfathiazole Crystalline Form (1.0wt%, High Concentration TCNF Solution)

[0059] (1) TCNF-induced crystal formation

[0060] 20 mg of sulfathiazole (S=4.85) was added to 16 mL of 1.0 wt% TCNF solution, and the mixture was stirred evenly and then cooled in an ice bath to allow natural crystallization.

[0061] (2) Crystal separation and drying

[0062] After the crystals were crystallized, they were separated with filter paper and washed with distilled water several times. The crystals were vacuum dried at 40°C for 24 hours to obtain a hexagonal crystalline sulfathiazole sample. Figure 5 As shown, its composition is III crystal form.

[0063] Results Analysis

[0064] Under the condition of 1.0wt% TCNF, the generated sulfathiazole crystals are mainly regular hexagonal crystals with large crystal size, showing high crystal consistency and good structural stability.

[0065] Through multiple embodiments, the present invention proves that by adjusting the TCNF concentration, the crystal formation and morphological changes of sulfathiazole can be effectively regulated. Under different TCNF concentrations, sulfathiazole crystals gradually change from flake and prismatic to hexagonal crystals, and the structural and morphological changes of the crystals are confirmed by PXRD, FTIR and microscopic analysis. This provides a new technical path for the optimization of sulfathiazole crystal forms.

Claims

1. Application of oxidized nanocellulose in regulating drug crystal form.

2. A method for regulating drug crystal form by oxidizing nanocellulose, characterized in that the steps include: The drug and the oxidized nanocellulose material are mixed in a solution and crystallized; The drug is in a supersaturated state in the solution, and the nucleation and growth of the drug crystal form can be controlled by adjusting the concentration of the oxidized nanocellulose material.

3. A method for regulating drug crystal form by oxidizing nanocellulose according to claim 2, characterized in that: The oxidized nanocellulose material solution is mixed with the drug and crystallized.

4. A method for regulating drug crystal form by oxidizing nanocellulose according to claim 2 or 3, characterized in that: The concentration of the oxidized nanocellulose material is 0.1 wt%-1 wt%.

5. A method for regulating drug crystal form by oxidizing nanocellulose according to any one of claims 2 to 4, characterized in that: The supersaturation S of the drug is 1-8.

6. A method for regulating drug crystal form by oxidizing nanocellulose according to any one of claims 2 to 5, characterized in that: The drugs include sulfathiazole, drugs having a sulfathiazole mother core or a sulfathiazole-like mother core, and drugs having a p-aminobenzenesulfonamide mother core or a p-aminobenzenesulfonamide-like mother core.

7. The method for regulating drug crystal form by oxidizing nanocellulose according to claim 6, characterized in that: The drugs are sulfathiazole, sulfamethoxazole, sulfadiazine, and sulfamethoxazole.

8. A method for regulating drug crystal form by oxidizing nanocellulose according to any one of claims 2 to 5, characterized in that: The crystals were cooled by ice bath.

9. A method for regulating drug crystal form by oxidizing nanocellulose according to any one of claims 2 to 5, characterized in that: The preparation method of oxidized nanocellulose TCNF solution includes: dispersing the raw material of oxidized nanocellulose in water, adding 2,2,6,6-tetramethylpiperidine-1-oxyl, sodium bromide and sodium hypochlorite to react, then adding ethanol to terminate the reaction, washing with water to neutrality, and obtaining oxidized nanocellulose TCNF solution.

10. The method for regulating drug crystal form by oxidizing nanocellulose according to claim 9, characterized in that: The raw material of the oxidized nanocellulose includes any one or any combination of pulp, cotton, wood and straw.

Citation Information

Patent Citations

  • New crystal forms of benzene sulfonamide thiazole and preparation method thereof

    CN104109159A

  • Polymorphic forms of an oxysterol and methods of making them

    CN108884125A

  • Method for preparing pharmaceutical composition and pharmaceutical composition

    CN112494430A

  • Preparation method of oxidized nanocellulose

    CN112694537A